Ethnobotanical Value of Myrianthus arboreus Used in Traditional Medicine by the Ngbaka Tribe (South-Ubangi), Democratic Republic of the Congo - Pascal N. Bobuya; Jetron M. Ngbolondo; Jean Pierre K.A. Zwave; Colette Masengo Ashande; Muhammad Ridwan; Koto-Te-Nyiwa Ngbolua (Budapest International Research in Exact Sciences (BirEx) Journal, 2022)
The aim of this study is to contribute to a better knowledge of the use of M. arboreus as a medicinal plant traditionally used in the treatment of common diseases by the Ngbaka people in the South Ubangi, Democratic Republic of the Congo. Based on free consent of the respondents, an ethnobotanical survey was carried out using a questionnaire among the Ngbaka healers. The aim of this study is to contribute to a better understanding of the use of M. arboreus as a medicinal plant traditionally used in the treatment of common diseases by the Ngbaka people in the South Ubangi. Based on consent of the respondents, an ethnobotanical survey was carried out using a questionnaire among the Ngbaka healers. The results obtained in this study allowed us to identify 23 diseases that are treated by Myrianthus arboreus. The organs of M. arboreus used for the treatment of diseases are mainly the leaf (96%), the bark of the stem (66%), the fruits and seeds (42%) and the roots (34%). The main methods of preparation of the organs were decoction (86%) and maceration (66%), while the administration of the recipes is predominantly via oral (86%) and cutaneous route (68%). The vast majority of respondents use M. arboreus organs for the treatment of abscesses (17 citations), sinusitis (15 citations) and tooth decay (15 citations), and wounds with 13 citations.  This work provides a source of information that can be used as a basis for pharmacological studies to assess therapeutic effectiveness.